Bio‐based composite granules with simultaneous biocontrol and phosphorus fertilization roles: Outcomes from a lab‐scale in vitro assessment. (23rd February 2022) - Favaro, Camila P.; Klaic, Rodrigo; Bettiol, Wagner; Ribeiro, Caue; Farinas, Cristiane Sanchez
Abstract: The use of phosphate rocks as low‐solubility phosphorus fertilizers has been promoted to reduce the environmental impacts of agriculture, but adequate nutrient uptake by plants depends on solubilization of the rock, driven by soil microorganisms. Here, investigation was made of the microbial solubilization of low‐solubility phosphate rocks, together with simultaneous bioprotective action involving the biocontrol of microorganisms. The aim was to enhance function and value by delivering two effects using a single bio‐based product, in accordance with the concept of a "bioreactor‐in‐a‐granule" system. A composite structure was developed, based on a starch matrix, comprising a combination of Trichoderma asperelloides, as a biocontrol agent, and Aspergillus niger, as an acidulant. A significant increase of up to 150% in P solubilization was achieved, indicating the positive effect of the microorganism‐composite interaction. In vitro assays showed that the ability of T. asperelloides to inhibit Fusarium oxysporum mycelial growth was maintained in the presence of A. niger . Moreover, the estimated cost of the composite granule (0.35 US/kg of product on a dry basis) revealed competitive. The results indicated that the association of T. asperelloides and A. niger is an effective way to increase nutrient availability and to inhibit plant pathogens, opening up possibilities for the design of multifunctional bio‐based fertilizer composites.